2020
DOI: 10.1021/acs.jpcc.9b08406
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of CeO2 Silanization by Spontaneous Breakage of Si–O Bonds through Facet Engineering

Abstract: Facet engineering is a new method of materials design with considerable potential for many technological applications. The present work uses DFT calculations to understand how this strategy can be used to accelerate the silanization of tetraethyl orthosilicate (TEOS) on the surface of ceria (CeO2), which is a key technology in biomedical and other fields. Cubic CeO2 nanoparticles with exposed {100} facets are shown to represent the most favorable morphology for silanization owing to (1) the facilitated adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Silanization is an effective grafting method for obtaining hydrophobically modified nanocellulose, by substituting OH groups on the surface with various Si-containing end groups [14,23,24,30]. Many studies used tetraethyl orthosilicate (TEOS) and methyltrimethoxysilane (MTMS) as organic precursors of alkoxysilane for the surface modification of CNCs, due to their low cost, low toxicity, and chemical stability [31,32]. It was reported that silanized cellulose nanofibers showed good adhesion with PHA based composites and contributed to the enhancement of their mechanical properties [23,33].…”
Section: Introductionmentioning
confidence: 99%
“…Silanization is an effective grafting method for obtaining hydrophobically modified nanocellulose, by substituting OH groups on the surface with various Si-containing end groups [14,23,24,30]. Many studies used tetraethyl orthosilicate (TEOS) and methyltrimethoxysilane (MTMS) as organic precursors of alkoxysilane for the surface modification of CNCs, due to their low cost, low toxicity, and chemical stability [31,32]. It was reported that silanized cellulose nanofibers showed good adhesion with PHA based composites and contributed to the enhancement of their mechanical properties [23,33].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Ce 3d attenuation of 19%, we estimate the silane coverage to have a thickness of approximately 1.5-2.2 nm (eqn (S1) †). [47][48][49] The O 1s peak at 528.9 eV, corresponding to lattice oxygen, 50 has reduced intensity after exposure to HSi(OMe) 2 Me, again consistent with overlayer coverage (Fig. 8b).…”
Section: Investigation Of Silane Reactions With Ceriamentioning
confidence: 76%
“…54–58 Facet engineering can be used as a powerful tool to enhance the modification of CeNPs, for example, silanization through the favorable adsorption of tetraethyl orthosilicate (TEOS) on the (100) facets and spontaneous breakage of the Si–O bonds of TEOS as the rate determining step for silanization. 59…”
Section: Physicochemical Properties Of Ceria Nanoparticlesmentioning
confidence: 99%